Effect of forming gas annealing on the degradation properties of Ge-based MOS stacks - Aguirre, Fernando Leonel (2018)
The influence of forming gas annealing on the degradation at a constant stress voltage of multi-layered germanium-based Metal-Oxide-Semiconductor capacitors (p-Ge/GeOx/Al2O3/High-K/Metal Gate) has been analyzed in terms of the C-V hysteresis and flat band voltage as a function of both negative and positive stress fields. Significant differences were found for the case of negative voltage stress between the annealed and non-annealed samples, independently of the stressing time. It was found that the hole trapping effect decreases in the case of the forming gas annealed samples, indicating strong passivation of defects with energies close to the valence band existing in the oxide-semiconductor interface during the forming gas annealing. Finally, a comparison between the degradation dynamics of Germanium and III-V (n-InGaAs) MOS stacks is presented to summarize the main challenges in the integration of reliable Ge–III-V hybrid devices.